Theoretical study for the inhibition ability of some bioactive imidazole derivatives against the Middle-East respiratory syndrome corona virus (MERS-Co) - Hassan Abdallah (Zanco Journal of Pure and Applied Sciences, 2019)
The Severe Acute Respiratory Syndrome (SARS) is a serious viral life-threatening and mortal respiratory illness caused by SARS-CoV. SARS-CoV plays an essential role in the viral replication cycle. It is considered a potential target for SARS inhibitor development. A series of twenty eight bioactive imidazole compounds as possible SARS-CoV inhibitors were designed and evaluated using computational calculations. Possible binding interaction modes were proposed by molecular docking studies. Among all studied compounds, compounds 5, 15 and 22 showed most potent inhibitory activity against SARS-CoV. These results indicated that these inhibitors could be potentially developed into anti-SARS drugs.